(untitled) (Bangladesh Journal of Nuclear Agriculture, 2023)
Blackgram is one of the most important pulse crops extensively grown in Bangladesh with multiple uses. An experiment was conducted to examine the suitability and productivity of a gamma irradiated pulse variety Binamash-2 in Kharif-II season for two consecutive years 2021 and 2022 over four locations, Mymensingh, Chapainawabganj, Gopalganj and Magura districts. The experiment was consisted of two varieties viz. Binamash-2 and BARI Mash-3. Binamash-2 produced higher seed yield than BARI mash3 at all four locations. Binamash-2 produced bolder seeds with early maturity than BARI mash3. The seed coat color and size of Binamash-2 was more attractive than BARI mash3 and farmers of four studied areas are very much interested to cultivate Binamash-2 in the upcoming years. Bangladesh J. Nuclear Agric, 37(2): 153-159, 2023